Prediction of SARS-CoV-2 3C-like protease (3CLpro) crystal structure to provide COVID-19 inhibitor design through computational studies - Taufik Muhammad Fakih; Dwi Syah Fitra Ramadhan (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Infectious diseases have lately become pandemic, posing a threat to global public health with the introduction of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), previously provisionally named 2019 novel coronavirus or 2019-nCoV). Technological advancements have increased the possibility of discovering natural inhibitor candidates capable of preventing and controlling COVID-19 infections. The SARS-CoV-2 3C-like protease (3CLpro) is critical for SARS-CoV-2 replication and is a prospective therapeutic target. This study aims to identify, evaluate, and explore the 3CLpro macromolecular structures from SARS-CoV and SARS-CoV-2, as well as their impact on angiotensin-converting enzyme 2 (ACE-2). The discovery of the two 3CLpro macromolecules revealed structural similarities in several regions. These findings were subsequently confirmed by performing protein-protein docking simulations to observe the interaction of 3CLpro with the active site ACE-2. With an ACE score of 701.41 kJ/mol, SARS-COV-2 3CLpro forms the strongest binding with ACE-2. As a result, the findings of this research can be used to guide the development of potential SARS-CoV-2 3CLpro inhibitors for the treatment of COVID-19 infectious diseases.